2016
DOI: 10.1127/anthranz/2016/0470
|View full text |Cite
|
Sign up to set email alerts
|

Sex determination by three-dimensional geometric morphometrics of craniofacial form

Abstract: The purpose of the present study is to define which regions of the cranium, the upper-face, the orbits and the nasal are the most sexually dimorphic, by using three-dimensional geometric morphometric methods, and investigate the effectiveness of this method in determining sex from the shape of these regions. The study sample consisted of 176 crania of known sex (94 males, 82 females) belonging to individuals who lived in Greece during the 20(th) century. The three-dimensional co-ordinates of 31 ecto-cranial la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 0 publications
0
16
0
2
Order By: Relevance
“…However, the study also proved that the gnathic index was correlated with the changes in the height of cranial vault, and facial height or cranial flexion between the two regions, which is not anadequate measure for prognathism. 4,29 The inferior and posterior vault shape represented the greatest shape differences between sexes in the American Black. However, the nasal and the orbital area represented the latest distinctions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the study also proved that the gnathic index was correlated with the changes in the height of cranial vault, and facial height or cranial flexion between the two regions, which is not anadequate measure for prognathism. 4,29 The inferior and posterior vault shape represented the greatest shape differences between sexes in the American Black. However, the nasal and the orbital area represented the latest distinctions.…”
Section: Discussionmentioning
confidence: 99%
“…20 Besides, Chovalopulou et al (2013) yielded 72% classification accuracy, 26 and revealed 81.8% and 84.3% classification accuracy in females and males, respectively. 29 Schlager and Rudell (2015) compared the variations on nose shape in the Germans and Chinese of both sexes by 3D geometric morphometric analysis on osseous tissue of the outer nose by utilizing the anatomical landmarks and semilandmarks. They investigated the discriminatory power of sexual dimorphism and the variations in population-specific shape concerning the bony nose on Chinese and German samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations